CIVIL LIABILITY FOR THE CONDUCTING OF EXTRAORDINARY GENERAL MEETINGS WITHOUT THE ATTENDANCE AND KNOWLEDGE OF SHAREHOLDERS (Analysis of Decision Number 92/Pdt.G/2020/PN. Yyk) - Jeremi (Journal of Constitutional Principles, 2025)
The Company may be examined for information or reports if it is suspected that the Company has committed an unlawful act that is detrimental to shareholders or other people or members of the board of directors or commissioners, an unlawful act and is detrimental to shareholders and other people. The obligation to hold an extraordinary general meeting without the presence and knowledge of shareholders in Decision Number 92 / Pdt.G / 2020 / PN.Yyk is a case that can be imposed by a judge with sanctions for the organizer to and return one hundred shares) NV Javaasche Bioscoop en Bouw Maatschappy filed an appeal after 14 days of the judge reading the decision